An Automatic Feature Based Face Authentication System - Arca, Stefano; Campadelli, Paola; Casiraghi, Elena; Lanzarotti, Raffaella (Neural Nets, 2006)
In this paper a fully automatic face verification system is presented. A face is characterized by a vector (jet) of coefficients determined applying a bank of Gabor filters in correspondence to 19 facial fiducial points automatically localized. The identity claimed by a subject is accepted or rejected depending on a similarity measure computed among the jet characterizing the subject, and the ones corresponding to the subjects in the gallery. The performance of the system has been quantified according to the Lausanne evaluation protocol for authentication.